Texture Analysis in Images with Differential Box Counting Algorithm - Praba, V. Lakshmi; Esakkiammal, S (International Journal of Computer Sciences and Engineering, 2025)
Fractal dimension is a one of the vital parameters in fractal geometry that find applications in the area of image processing. Image analysis is a high-level image processing technique which includes texture analysis. Texture analysis characterizes the regions in an image, based on their texture content. It categorizes texture qualities as roughness, smoothness, silkiness, bumpiness, etc. The image intensities are transformed to fractal dimension domain to carry out texture analysis. In this paper, determining the texture for two images- smooth image and coarse image is considered. Differential Box Counting algorithm is applied in the considered two images with different textures. The performance metrics considered are, fractal dimension average, fractal dimension standard deviation and lacunarity. The differential box counting algorithm with different pixels from different regions of the same image is implemented and the obtained results are analyzed